Correction: A new GTF2I-BRAF fusion mediating MAPK pathway activation in pilocytic astrocytoma. - Tajana Tešan Tomić; Josefin Olausson; Annica Wilzén; Magnus Sabel; Katarina Truvé; Helene Sjögren; Sándor Dósa; Magnus Tisell; Birgitta Lannering; Fredrik Enlund; Tommy Martinsson; Pierre Åman; et al. (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0175638.].